Dynamics of T cell subpopulations and plasma cytokines during the first year of antineoplastic therapy in patients with breast cancer: the BEGYN-1 study - Elisabeth Kaiser; Regine Weber; Melanie Hirschstein; Hala Mazid; Emilie Marie Suzanne Kapps; Muriel Charlotte Hans; Michelle Bous; Sybelle Goedicke-Fritz; Gudrun Wagenpfeil; Michael Zemlin; Erich-Franz Solomayer; Carolin Müller; et al. (Breast Cancer Research)
Abstract Background The role of T cell immunity during antineoplastic therapy is poorly understood. In the BEGYN-1 study, patients with breast cancer underwent quarterly assessments prior to and during antineoplastic therapy over a period of 12 months. Methods We used flow cytometry and multiplex immunoassays to quantify 25 T cell subpopulations and seven T cell associated plasma cytokines in peripheral blood from 92 non-metastatic breast cancer patients, respectively. In addition, the association between T cell dynamics and the outcome of patients undergoing neoadjuvant chemotherapy was investigated. Results In patients undergoing chemotherapy, a significant reduction in T helper (Th) cells, particularly naïve central and effector cells and thymus positive Th cells, was observed over time. Interestingly, Th1 immune response-associated cytokines (IL-12, TNF, IFN-γ) declined while Th2 cells and cytotoxic T cells increased over time. Conclusions We conclude that in breast cancer patients, chemotherapy is associated with a transition from a Th1 immune response towards Th2 and an increase in cytotoxic T cells, whereas in patients without chemotherapy, these alterations were less pronounced. Future studies should clarify whether patterns of T cell subsets or plasma cytokines can be used as biomarkers to monitor or even improve therapeutic interventions. Graphical abstract